Peran Lembaga Keuangan Syariah Dalam Pemberdayaan Usaha Mikro Kecil dan Menengah (Studi Kasus Bank Syariah Mandiri Kantor Cabang Lumajang) - Maryani Maryani; Zainal Abidin (Jurnal Manajemen dan Bisnis, 2021)
This study aims to describe the role of Islamic financial institutions in the empowerment of micro, small and medium enterprises. This research use desciptive qualitative approach. The results of this study indicate that BSM helps UMKM business progress through financing with competitive profit sharing and supports UMKM business development through programs, such as the blessing of Ramadan with very light profit sharing, year-end programs as well as light profit sharing and also finance the renovation of business premises, procurement merchandise, and procurement of tools and facilities and infrastructure for business.